Evaluating Educational Credentials of Teachers as Predictor of Effective Teaching: A Pupil Fixed-Effect Modeling Approach - Liu, Ji (Frontiers in Psychology, 2021)
Many factors serve as predictors of effective teaching, however, there is an ongoing debate regarding whether teachers’ own educational credential is indicative of their contribution to educational success. Utilizing pupil fixed-effect modelling and China Education Panel Survey dataset (n=5,032), this study evaluates the extent to which teachers holding at least a Bachelor of Education degree perform better than those who do not, in terms of pupil learning gains over the course of a full academic year. Empirical results from the pupil fixed-effect model indicate that mean learning gain is 0.042 standard deviations (95% confidence interval: 0.008-0.083, p=0.040) higher in pupils who studied with teachers holding higher educational credentials (at least a B.Ed. degree) than those with lower educational credentials. This effect translates to approximately one month of additional learning per year, which is significant considering the potential compounding aggregation effects over the course of pupils’ entire education career. This study adds new evidence that highlights the importance of teacher educational credentials as predictor of effective teaching, that better educated teachers can lead to improved pupil learning gains.